Comparison of Sodium Imbalance in Diabetics and Non-Diabetics Presenting with Sepsis - Odho, Ali Ahmed; Bhatty, Shaheen (Indus Journal of Bioscience Research, 2025)
Background: Patients with diabetes are more likely to get infection and, as a result, sepsis. Sepsis is the largest cause of intensive care unit (ICU) admissions, resulting in a huge healthcare burden. Despite extensive research on sepsis and electrolyte disturbances, in diabetic individuals there is a notable gap in studies comparing sodium imbalances in diabetic versus non-diabetic patients with sepsis. Therefore, the current study aims to explore these differences in sodium level in diagnosed patients of sepsis with and without diabetes. Methodology: It was a cross-sectional study conducted at Department of Medicine, Dr. Ruth K.M. Pfau Civil Hospital, Karachi from January to March 2025. The required sample size for this study after calculation was 113 patients however, the data was gathered for 120 patients 60 patients with diabetes and sepsis and other 60 without diabetes with sepsis. The study participants were recruited via non-probability consecutive sampling. The set inclusion criteria was patient of age between 18-70 years, either gender and patients presenting within 24–72 hours of sepsis onset. A 5 cc blood sample was drawn by a trained phlebotomist using aseptic techniques for serum sodium level assessment. Serum sodium levels were analyzed using flame spectrometry. All patients with sepsis were managed according to the hospital's standard treatment protocol. Data was recorded on a predesigned proforma, including the occurrence and type of sodium imbalance (hyponatremia or hypernatremia). Results: There was a significant difference (p-value <0.001) between the sodium level of diabetic and non-diabetic patients with sepsis. Most of the diabetic patients had hyponatremia (sodium level < 135 mEq/L). There was no significant difference (p-value = 0.221) in development of symptoms of sepsis among study participants of both the groups. Conclusion: Patients with sepsis and diabetes were presented with hyponatremia (sodium level < 135 mEq/L) in our study setting.